European and Integration Studies - N. Yu. Kaveshnikov (Vestnik MGIMO-Universiteta)
Soviet scientific school of pan-European integration studies began to emerge in the 1960s at the Institute of World Economy and International Relations (Russian Academy of Science). Among the leading scientists who have developed methodological approaches of Soviet integration studies were M.M. Maximova, Y.A. Borko, Y. Shishkov, L.I. Capercaillie. Later, a new center for integration studies became the Institute of Europe, created in 1987. It was led by such renowned scientists as Academicians V.V. Zhurkin and N.P. Shmelev. In the 1980s the subject of the integration process in Europe attracted attention of experts from MGIMO. An important role in the development of school of integration research in the USSR was played by a MGIMO professor, head of the chair of history of international relations and foreign policy of the USSR V.B. Knyazhinskiy. His work contributed to the deliverance of the national scientific community from skepticism about the prospects for European integration. Ideas of V.B. Knyazhinsky are developed today in MGIMO by his followers A.V. Mal'gin and T.V. Ur'eva. In the mid-1990s, having retired from diplomatic service, professor Yu. Matveevskiy started to work at MGIMO. With a considerable practical experience in the field, he produced a series of monographs on the history of European integration. In his works, he analyses the development of integration processes in Western Europe from their inception to the present day, showing the gradual maturation of the necessary spiritual and material prerequisites for the start of integration and traces the various stages of the "integration". In the late 1990s, the growing demand from the domestic business and government for professionals who are capable of interacting with the European Union, has produced the necessary supply in the form of educational programs based on accumulated scientific knowledge. Setting up a discipline "European Integration" was a major step in the development of domestic science school integration research. The creation in 2003 at MGIMO of the first in Russia Department of European integration was a necessary and logical step.